"Do piezoelectric and piezomagnetic sensors like, BaTio2, CoMnF2, CoF2felicitate propagation of electromagnetic signals induced dweue to stress within subsurface of crust and hence display pre-seismic signature?". (2021) - Verma, Umesh Prasad; Mishra, Akhilesh Kumar; Sinha, Madhurendra Nath
Abstract: Piezoelectric and Piezomagnetic materials like PbTio2, quartz, PbGaTio2 (Gallium Titanate) are quite susceptible to the implied stress and respond proportionately in direction and magnitude tn terms of electric voltage. The intensity, magnitude and direction depends on the configuration and dimension of the material configurated, For desired voltage a demarcated coupling factor are designed to respond accordingly. Similar way the piezomagnetic substances are responding Viz: CoF2 and MnF2 to the applied mechanical stress in proportionate manner. Objectives are targeted to capture the piezomagnetic signals as confirmatory and Piezoelectric signals induced due to stress applied as pre -seismic signature in the subsurface of crustal region.